Preclinical evaluation of the AR inhibitor enzalutamide in triple-negative breast cancer cells. Issue 4 (April 2016) - Caiazza, Francesco; Murray, Alyson; Madden, Stephen F; Synnott, Naoise C; Ryan, Elizabeth J; O'Donovan, Norma; Crown, John; Duffy, Michael J
Abstract: The androgen receptor (AR) is present in approximately 80% of invasive breast cancer patients and in up to 30% of patients with triple-negative breast cancer (TNBC). Therefore, our aim was to investigate the targeting of AR as a possible hormonal approach to the treatment of TNBC. Analysis of 2091 patients revealed an association between AR expression and poor overall survival, selectively in patients with the basal subtype of breast cancer, the vast majority of which are TNBC. IC50 values for the second-generation anti-androgen enzalutamide across 11 breast cancer cell lines varied from 4 µM to >50 µM. The activity of enzalutamide was similar in TN and non-TN cell lines but was dependent on the presence of AR. Enzalutamide reduced clonogenic potential and cell growth in a 3D matrix in AR-positive cells. In addition, enzalutamide also inhibited cell migration and invasion in an AR-dependent manner. Enzalutamide appeared to mediate these processes through down-regulation of the transcription factors AP-1 and SP-1. The first-generation anti-androgen flutamide similarly blocked cell growth, migration and invasion. AR-positive TNBC cells clustered separately from AR-negative cells based on an androgen-related gene expression signature, independently of TNBC subtype. We conclude that targeting of the AR with drugs such as enzalutamide may provide an alternative treatment strategy for patients with AR-positive TNBC.